2019
DOI: 10.1021/jacs.9b03036
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of a Putative Intermediate in the Cytochrome c Nitrite Reductase (ccNiR)-Catalyzed Reduction of Nitrite: Implications for the ccNiR Reaction Mechanism

Abstract: Cytochrome c nitrite reductase (ccNiR) is a periplasmic, decaheme homodimeric enzyme that catalyzes the six-electron reduction of nitrite to ammonia. Under standard assay conditions catalysis proceeds without detected intermediates, and it has been assumed that this is also true in vivo. However, this report demonstrates that it is possible to trap a putative intermediate by controlling the electrochemical potential at which reduction takes place. UV/vis spectropotentiometry showed that nitrite-loaded Shewanel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 70 publications
(206 reference statements)
5
49
0
Order By: Relevance
“…The UV-Vis and EPR spectra (Fig. S2 and S3) are consistent with previously characterized NrfA enzymes (10,(22)(23)(24).…”
Section: G Lovleyi Nrfa Was Heterologously Overexpressed In S Oneidensissupporting
confidence: 87%
“…The UV-Vis and EPR spectra (Fig. S2 and S3) are consistent with previously characterized NrfA enzymes (10,(22)(23)(24).…”
Section: G Lovleyi Nrfa Was Heterologously Overexpressed In S Oneidensissupporting
confidence: 87%
“…The rst PCET forms a {FeNO} 7 species (with protonation of Arg 114 residue) which subsequently generates {FeHNO} 8 species through another PCET process, releasing only a trace amount of the {FeNO} 7 intermediate. 11,67 In contrast, Cd 1 NiR undergoes an electron transfer (ET) from cytochrome c, forming the {FeNO} 7 intermediate, which releases NO rapidly (k off $ 200 s À1 ). 13,19 There is an extensive debate on whether the NO is released from 69 suggested that maximum ruffling was present in {FeTPC-NO} 7 species, which possess a chlorin ring (see the ESI, Section 9 †), and had a relatively strong Fe-NO bond.…”
Section: Discussionmentioning
confidence: 99%
“…Ferrous heme–nitrosyl complexes, ls-{FeNO} 7 in the Enemark–Feltham notation, have been extensively studied with many spectroscopic and theoretical methods as described in Section . Most recently, Pacheco and coworker were able to trap a ls-{FeNO} 7 intermediate in S. oneidensis NrfA, using spectro­potentiometry . Previously, it had been shown by protein film voltammetry experiments that catalytic turnover in S. oneidensis NrfA requires an applied potential of at least −120 mV (vs SHE), which lies below the midpoint potential for the formation of the ls-{FeNO} 7 complex. , This indicates that it might be possible to trap the ls-{FeNO} 7 intermediate if a more positive potential is applied that stalls the catalytic cycle, thus preventing ammonia formation.…”
Section: The Nitrogen Cyclementioning
confidence: 99%
“…c nitrite reductases (C c NIRs), following the reaction: The active site heme of C c NIRs is unusual, as it shows axial Lys coordination, although the significance of the proximal Lys for catalysis is unclear. Notably, nitrite reduction to ammonia by C c NIRs is proposed (from computational studies) to involve the complete set of heme-based ls-{FeNO} 6−8 intermediates, but details of the mechanism and experimental characterization of such reaction intermediates are lacking . The DNRA pathway is particularly interesting as a natural mechanism to convert nitrite and nitrate back into ammonium (i.e., fertilizer), instead of converting them into gaseous products and losing nitrogen from the soil …”
Section: Introductionmentioning
confidence: 99%